Peramalan Harga Jagung Kering di Tingkat Petani di Indonesia: Pendekatan Model ARMA - Januarta, Moh. Aga Indra; Rahman, Rena; Salsabila, Farah; Fatikhuz, Dimas (Hasanuddin University, 2025)
Corn is one of the most important agricultural commodities in Indonesia, serving as a vital source of food and animal feed. With increasing demand and price fluctuations, forecasting the price of dry maize using the ARMA method becomes essential to support better decision-making by farmers and stakeholders. This study aims to forecast the farm-gate price of dry maize for the years 2025 to 2026. The forecasting method employed in this research is the Autoregressive Moving Average (ARMA) model. The results indicate that the best-fitting ARMA model is the one with parameters one, zero, thirty-six, which does not require prior differencing, as the data obtained from FAOSTAT and BAPANAS has been found to be stationary. The forecast results suggest that maize prices are expected to experience a gradual downward trend from May 2025 to December 2026. The highest price is projected to occur in December 2025 at Rp 4,933 per kilogram, while the lowest price is estimated for December 2026 at Rp 4,696 per kilogram. Although there are minor fluctuations in the middle of the period, the overall trend indicates a medium-term decline in maize prices.